Penggunaan Media Sosial dan Aktivitas Fisik pada Remaja Tingkat Sekolah Menengah Pertama (SMP) Tahun 2018 - Imam Waluyo; Imas Dwi S Dwi S; M Arsyad Subu; Djajang Djajang; Slamet Slamet S; Rinto Agustino (Jurnal Ilmu dan Teknologi Kesehatan, 2019)
Users of social networking sites are consistently logged online to communicate and interact with other users. Social networking sites are one of the most popular forms of social media, especially among teenagers, and are an alternative email as a means of instant communication between friends. This study aims to examine the Correlation between social media use with physical activity on junior high school adolescent. The study a futher analysis of previous research data with the 315 sample of Junior High School adolescent, cross sectional metode use, and Data collected using instrumen Social Networking Use Scale and Physical Activity Questionnaire for Adolescent. The result: low user of SNS with 78 student (24.8%), average user of SNS 143 student (45.4%), high user of SNS 81 student (25.7%), extremely high user of SNS 13 student (4.1%), and physical activity low activity 54 student (17.1%), moderate activity 181 student (57.5%), vigorous activity 80 student (25.4%). the results show that corelation between social media use with physical activity corellation weak with r=0.005 stated is weak, statistically it is not significant p= 0.928 (p>0.05). In this study, we found that there is a weak correlation between social media use with physical activity, and statistically it is not significant